Know the heretics - Holcomb, Justin S., 1973- (Grand Rapids, Michigan : Zondervan, 2014)
There is a lot of talk about heresy these days. The frequency and volume of accusations suggest that some Christians have lost a sense of the gravity of the word. On the other hand, many believers have little to no familiarity with orthodox doctrine or the historic distortions of it. What's needed is a strong dose of humility and restraint, and also a clear and informed definition of orthodoxy and heresy. Know the Heretics provides an accessible 'travel guide' to the most significant heresies throughout Christian history. As a part of the KNOW series, it is designed for personal study or classroom use, but also for small groups and Sunday schools wanting to more deeply understand the foundations of the faith. Each chapter covers a key statement of faith and includes a discussion of its historical context; a simple explanation of the unorthodox teaching, the orthodox response and a key defender; reflections of contemporary relevance; and discussion questions. - Publisher.
Foreword / Thomas C. Oden -- Introduction : Why heresy? -- Judaizers : the old rules still apply -- Gnostics : God hides messages for the enlightened -- Marcion : vengeful Yahweh versus gentle Jesus -- Docetists : the spiritual is good, the physical is evil -- Mani : God must be freed -- Sabellius : one actor and three hats -- Arius : Jesus is a lesser god -- Apollinarius : Christ may be human, but his mind is divine -- Pelagius : God has already given us the tools -- Eutyches : Christ as a new kind of being -- Nestorius : Christ's divinity must be shielded -- Socinus : the trinity is irrelevant and Jesus' death is only an example -- Conclusion -- Appendix 1 : The Council of Nicaea and the Nicene Creed -- Appendix 2 : Antioch and Alexandria : two understandings of Christ.
Includes bibliographical references.
Keywords: Apologetics; Christian heresies; Christian heretics